2018
DOI: 10.3389/fimmu.2018.02851
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biodegradable Polymeric Microparticles Facilitate Scarless Wound Healing by Promoting Re-epithelialization and Inhibiting Fibrosis

Abstract: Despite decades of research, the goal of achieving scarless wound healing remains elusive. One of the approaches, treatment with polymeric microcarriers, was shown to promote tissue regeneration in various in vitro models of wound healing. The in vivo effects of such an approach are attributed to transferred cells with polymeric microparticles functioning merely as inert scaffolds. We aimed to establish a bioactive biopolymer carrier that would promote would healing and inhibit scar formation in the murine mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…However, whereas in the latter host 70–80% of MaSp2 was in the water-insoluble cellular fraction, in P. pastoris 60% was in the soluble fraction. The proteins are being developed into matrices for tissue engineering and drug delivery (Agapov et al, 2009; Moisenovich et al, 2016; Moisenovich et al, 2011; Nosenko et al, 2018).…”
Section: Protein Polymers Produced In P Pastorismentioning
confidence: 99%
“…However, whereas in the latter host 70–80% of MaSp2 was in the water-insoluble cellular fraction, in P. pastoris 60% was in the soluble fraction. The proteins are being developed into matrices for tissue engineering and drug delivery (Agapov et al, 2009; Moisenovich et al, 2016; Moisenovich et al, 2011; Nosenko et al, 2018).…”
Section: Protein Polymers Produced In P Pastorismentioning
confidence: 99%
“…In fact, studies have demonstrated that macrophages in contact with several biomaterials produce lower levels of proinflammatory cytokines, such as IL-1β, CXCL8(IL-8), IL-12 and TNF-α, and higher levels of immunosuppressive cytokines, such as IL-10 [ 11 , 40 , 41 ]. Although the mechanism is not clear, NCM characteristics, such as physical properties (geometry, topography and porosity) and biochemical properties (surface chemistry, ligand functionalization and degradation mode) have been determined as critical factors in the host response to the material [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microparticles based on recombinant spidroin rS1/9 with sizes of 100 and 300 μm were obtained as described in Nosenko et al (2018) . Microparticles were stored in 70% ethanol and washed five times in PBS prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…Using the protocols described earlier regenerated fibroin was obtained and later lyophilized (Nosenko et al, 2018). Recombinant protein rS1/9 produced by yeast cells carrying gene rS1/9 was isolated from lysed cells, purified by ion-exchange chromatography in fast protein liquid chromatography up to 95% purity and lyophilized.…”
Section: Formation Of Filmsmentioning
confidence: 99%